2017
DOI: 10.1136/archdischild-2016-311050
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based approaches to childhood stunting in low and middle income countries: a systematic review

Abstract: ObjectiveWe systematically evaluated health and nutrition programmes to identify context-specific interventional packages that might help to prioritise the implementation of programmes for reducing stunting in low and middle income countries (LMICs).MethodsElectronic databases were used to systematically review the literature published between 1980 and 2015. Additional articles were identified from the reference lists and grey literature. Programmes were identified in which nutrition-specific and nutrition-sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
132
0
12

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(149 citation statements)
references
References 28 publications
5
132
0
12
Order By: Relevance
“…The 6 interventions with a positive impact on stunting had small effects, with the mean improvement close to the typical value for measurement error. Another systematic review evaluated the effectiveness of urban and rural health and nutrition programmes in low income nations to prevent stunting of under-5 year old infants and children (Hossain et al 2017). Literature between 1980 and 2015 was searched and only 14 programmes were identified that effectively reduced stunting based on the criteria of an annual rate of reduction ≥ 3%.…”
Section: Discussionmentioning
confidence: 99%
“…The 6 interventions with a positive impact on stunting had small effects, with the mean improvement close to the typical value for measurement error. Another systematic review evaluated the effectiveness of urban and rural health and nutrition programmes in low income nations to prevent stunting of under-5 year old infants and children (Hossain et al 2017). Literature between 1980 and 2015 was searched and only 14 programmes were identified that effectively reduced stunting based on the criteria of an annual rate of reduction ≥ 3%.…”
Section: Discussionmentioning
confidence: 99%
“…Working with international partners such as World Health Organisation (WHO) and United Nations Children's Fund (UNICEF), governments in SSA have put in place various interventions to improve child growth by addressing stunting in the region [4,5]. However, the implementation of these programmes tends to focus more on child growth deficiencies and how to protect children against risk factors of growth deficiencies [6,7]. Therefore, it may be difficult to directly attribute the effects of the programmes on child healthy growth outcomes, except to infer that reduction in stunting implies an increase in healthy growth.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Hossain et al . recently showed programmes that effectively reduced stunting in LMIC most commonly implemented interventions of nutrition education and counselling, growth monitoring and promotion, immunisation, water, sanitation and hygiene, and social safety nets. These approaches will require strengthening of the public health services to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of robust evidence available on what works, and so best in class interventions that prevent malnutrition in children should be assessed for effectiveness for children with disabilities in LMIC [57]. For instance, Hossain et al [35] recently showed programmes that effectively reduced stunting in LMIC most commonly implemented interventions of nutrition education and counselling, growth monitoring and promotion, immunisation, water, sanitation and hygiene, and social safety nets. These approaches will require strengthening of the public health services to be effective.…”
Section: Discussionmentioning
confidence: 99%